Beyond Trikafta: new models to assess tissue dependent rescue of N1303K-CFTR - Pranke, Iwona; Capurro, Valeria; Chevalier, Benoit; Pesce, Emanuela; Tomati, Valeria; Pastorino, Cristina; Kelly-Aubert, Mairead; Hatton, Aurelie; Dreano, Elise; Lena, Mariateresa; Bocciardi, Renata; Zara, Federico; et al. (Frontiers in Pharmacology, 2025)
RationaleRespiratory status of people with Cystic Fibrosis (pwCF) carrying N1303K is improved by Elexacaftor/Tezacaftor/Ivacaftor (ETI) but, contrary to other mutations, the impact on sweat test results is limited.MethodsTo explore this discrepancy, we implemented new sweat gland and respiratory cell lines stably expressing Wild type (WT)-, F508del- and N1303K-CFTR. CFTR dependent chloride (Cl−) and bicarbonate (HCO3-) transport was measured by short circuit current in these new models and in primary Human Nasal Epithelial Cells (HNECs). CFTR expression was evaluated by Western blot.ResultsIn the airway and the sweat gland cells expressing F508del-CFTR, ETI induced maturation of CFTR and increased Cl− transport. In the respiratory cell lines and HNECs, N1303K-CFTR generated both immature and mature forms of CFTR. Correction by ETI increased CFTR amounts without promoting its maturation and improved Cl− secretion. N1303K-CFTR channel activity was markedly increased by co-potentiation of IVA with Apigenin. In the sweat gland, N1303K-CFTR was expressed as a globally misfolded protein, non-rescuable by ETI. API treatment to 2 patients improved FEV1 without lowering sweat Cl- content.ConclusionN1303K-CFTR shows tissue specific correction and suboptimal response to ETI which can be improved by API.